ANALISIS SEMIOTIKA TENTANG REPRESENTASI EMANSIPASI WANITA DALAM FILM YUNI - Hasan Ales Sandro (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study examines the social phenomenon of patriarchal culture and women’s emancipation as portrayed in audio-visual media. This research examines how the message of women's emancipation is represented through visual and verbal signs in Yuni (2021), a film directed by Kamila Andini. The research employs Roland Barthes' semiotic approach, focusing on three levels of meaning: denotation, connotation, and myth. A descriptive qualitative method is used, with data gathered through the analysis of key scenes in the film and supported by relevant literature on women's emancipation and patriarchal culture. The findings reveal that Yuni represents women's emancipation through various symbols, dialogues, and actions of the protagonist, Yuni, as well as supporting characters such as Suci and Bu Lilis. These representations include resistance against early marriage, the struggle for educational rights, bodily autonomy, and defiance against patriarchal norms. The semiotic analysis demonstrates that the film not only portrays the pressures of patriarchal culture but also offers a narrative of liberation through the subversive actions of its female characters. This study contributes theoretically to film semiotics and practically to the understanding of women's emancipation in media. Furthermore, it is expected to foster critical awareness in society regarding the importance of gender equality and women's rights across various aspects of life.Keywords: Semiotics, Women's Emancipation, Yuni Film, Roland Barthes, Patriarchy.